Interaksi Antara Laporan Keuangan Konservatif dan Insentif Manajerial dalam Pengambilan Keputusan: Tinjauan Literatur - Ruslaini Ruslaini; Benardi Benardi; Tanti Sugiharti (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This study examines the interaction between conservative financial reporting and managerial incentives in decision-making, using a qualitative approach through a literature review. Conservative financial reporting plays a crucial role in enhancing the transparency and accuracy of information utilized by managers in the decision-making process. On the other hand, optimally designed managerial incentives can encourage managers to value and utilize the accounting information presented conservatively. The findings indicate that accounting conservatism can reduce the risk of inappropriate decision-making, although it may also pose potential risks of avoidance towards necessary investments for company growth. This research provides insights into the importance of balancing the implementation of conservative financial reporting and managerial incentives, as well as its implications for corporate performance. The results of this study are expected to serve as a reference for company management in designing more effective incentive systems and reporting.